Physical and Chemical Analysis of Fish Feed Based on Fermentation of Kelakai Leaf (Stenochlaena palustris (Burm.F.) Bedd) - Fauzana, Noor Arida; Redha, El; Adriani, Muhammad; Ilmiati, Qori’ah; Siskawati, Multi (International Journal of Environment, Agriculture and Biotechnology, 2022)
Kelakai (Stenochlaena palustris) can be used as an ingredient in fish feed because it has a high protein content. The problem with the use of kelakai for fish feed is that the crude fiber content is quite high, and the improvement of this nutritional value can be done through the fermentation process. The purpose of this study was to analyze the physical and chemical properties of fish feed based on fermented kelakai leaves. The research was conducted at the Nutrition Laboratory, Faculty of Fisheries and Marine Affairs, Lambung Mangkurat University Banjarbaru, South Kalimantan Province for ± 1.5 months. This study used a completely randomized design (CRD) with 3 treatments, namely Treatment (A) non-fermented kelakai leaf-based feed, treatment (B) fermented kelakai leaf-based feed with a dose of probiotics 5%, and Treatment (C) Fermented feed based on a 10% dose of probiotics, with test parameters namely physical test and chemical test of feed. The results showed that the longest durability of feed was destroyed after 1 hour 02 minutes in the non-fermented treatment, while the best feed buoyancy was in the treatment of kelakai leaf fermentation-based feed at a dose of 5% for 43.75 seconds. Kelakai leaf fermented feed with doses of 0%, 5%, 10% showed the value of protein content (25.78%-26.28%), crude fiber (7.67%-7.96%), fat (3.32%- 6.88%), and contains 8 essential amino acids (L-Phenylalanine, L-Leucine, L-Valine, L-Arginine, L-Lysine, L-Leucine, L-Threonine, L-Histidine) and 7 non-amino acids. essential oils (L-Serine, L-Glutamic acid, L-Alanine, glycine, L-Aspartic, L-Tyrosine, L-Proline) where the highest value was in the fermented feed based on the 5% dose of tapioca flour.